ANALISIS KEPUASAN PASIEN RAWAT JALAN TERHADAP IMPLEMENTASI SISTEM PENDAFTARAN ONLINE DI RUMAH SAKIT SWASTA ISLAM SITI RAHMAH - Rika Amran; Ziqro Wahyuni; Febianne eldrian; Dhina Lydia Lestari; Hiddayaturrahmi Hiddayaturrahmi; meisya jovanka syahara meisya jovanka syahara (Nusantara Hasana Journal, 2026)
Digitizing healthcare services through online registration is a crucial strategy for reducing waiting times and queues. This study aims to evaluate outpatient satisfaction with the use of the online registration application at RSI Siti Rahmah Padang. Using a descriptive observational design with a cross-sectional approach, data were collected from 85 samples through a simple random sampling technique from June to October 2024. The research instrument was a questionnaire measuring service quality and satisfaction levels. The results showed that the majority of respondents were in the productive age group (26-35 years), female (67.1%), and had a bachelor's degree (47.1%). 84.7% of respondents assessed the service quality as good, and 82.4% expressed satisfaction with the system. These findings confirm that the effectiveness of the hospital management information system (SIMRS) is positively correlated with patient experience, although ongoing education is still needed to minimize manual registration.